The role of scientific societies and the academic world in the ongoing updating of the colombian health social security system's benefits plan - Hernando Gaitán (Federación Colombiana de Obstetricia y Ginecología, 2015)
The benefits' plan has been defined as "providing people with a set of activities, procedures, supplies, and recognition, aimed at maintaining or recovering their health and avoiding affecting their economic capacity derived from temporary disability caused by general illness, maternity, and incapacity, handicap or invalidity arising from the risk of accidents at work and professional disease."1 Colombian law 100 initially created three benefit plans: the basic attention plan (plan de atención básica -PAB), the obligatory contribution-type plan (plan obligatorio de salud contributivo POS) and the subsidised obligatory health plan (plan obligatorio de salud subsidiado POSS), being different in their origin and regarding the services which they included for the benefiting population. Constitutional Court ruling T 760/2008 ordered the following regarding benefit plans, "measures should be adopted for eliminating uncertainty about the content of benefit plans and they must be periodically updated; benefit plans (POS and POSS) must be unified, firstly in the case of children and then, progressively, in the case of adults, bearing their suitable funding in mind."2